The use of web technologies and tools in developing an interactive internet programming online tutorial (IIPOT) / Iznora Aini Zolkifly - Zolkifly, Iznora Aini (2004)
This paper will discuss the use of various web technologies and tools in developing an interactive online tutorial for Internet Programming course at Universiti Tun Abdul Razak. This interactive online tutorial consists of Course preview, Courseware (includes Quiz and Glossary), Assignment, Q & A, e-mail, forum and On-Iine Tutorial (OLT). Web programming languages has been used in the courseware development such as JavaScript for Quiz and Practices module, Active Server Pages with web database for Assignment module, HTML and DHTML for notes, and XML for forum. Collaboration tool such as CENTRA Symposium is used for On-Line Tutorial (OLT) session where lecturers and students can communicate with each other through the text chat or using audio set, and at the same time can browse the slides given on the screen whiteboard. Animated Pedagogical Agent such as Microsoft Agents has been used as one of the tools to assist students during their learning phase. This combination of asynchronous and synchronous communications together with the integration of web programming language and tools helps the students to study at their own pace. As a result, students can do the exercises and learn better in flexible and interactive ways.